Prevalence of bovine milk pathogens in Azorean pastures: mobile versus fixed milking machines. Issue 1 (25th October 2016) - Azevedo, C.; Pacheco, D.; Soares, L.; Moitoso, M.; Maldonado, J.; Guix, R.; Simões, J.
Abstract : The aims of the present study were (1) to evaluate the influence of using mobile (n=47) or fixed (n=45) milking machines in Azorean herds on the apparent prevalence of several milk pathogens in bulk tank milk (BTM) and (2) to determine whether separated subclinical mastitic cows can serve, in real time, as predictors of milk pathogen prevalence for the remaining animals at the herd level. The use of a mobile or fixed milking machine influenced (P≤0.05) the prevalence of Staphylococcus aureus (72.3 per cent; n=34 v 51.1 per cent; n=23, respectively) and Klebsiella species (46.8 per cent; n=22 v 26.7 per cent; n=12, respectively). S aureus (95 per cent CI OR 1.1 to 6.0) and Klebsiella species (95 per cent CI OR 1.0 to 5.8) were 2.5 times more likely to increase in the BTM of herds using mobile milking machines. The prevalence of coagulase‐negative staphylococci (100 per cent; n=92), Escherichia coli (75.0 per cent), Corynebacterium bovis (57.6 per cent), Enterococcus species (55.4 per cent), Streptococcus dysgalactiae (51.1 per cent), Streptococcus uberis (41.3 per cent), Actinomyces pyogenes or Peptostreptococcus indolicus (41.3 per cent) and Streptococcus agalactiae (32.6 per cent) in BTM remained similar among the herds. κ coefficients were always <0.70, indicating intra‐herd disagreement of the prevalence of milk pathogens between BTM and separated milking cows. Milking hygiene should be improved in pastures, focusing specifically on herds that use a mobile milking machine. The segregated cows at milking time are not good predictors of milk pathogens in BTM.